Key factors for overcoming psychological insulin resistance: A qualitative study in Japanese people with type 2 diabetes. Issue 3 (June 2022) - Okazaki, Kentaro; Takahashi, Noriyuki; Shingaki, Tomotaka; Perez-Nieves, Magaly; Stuckey, Heather
Abstract: Aims: We report the key factors that motivate reluctant Japanese people with type 2 diabetes (T2D) to initiate insulin treatment. Methods: Participants were asked questions pertaining to 2 primary areas of exploration in a concurrent mixed methods approach: (a) understanding people's thoughts and perceptions before and after insulin initiation and any related factors; and (b) exploring the reasons behind people's responses. Data were analyzed using Steps for Coding and Theorization. Results: Participant responses broadly related to 3 themes which influence insulin initiation; 1. Advice from a health care provider (HCP) that insulin is an appropriate treatment; 2. Demonstration by HCPs on how to use the insulin pen/needle and the injection process; and 3. Resignation/surrender/acceptance of insulin, where participants felt there was no other choice but to commence insulin. Conclusions: Based on the 3 identified themes, it is important for HCPs to explain the benefits of insulin and demonstrate and explain the injection procedure to reluctant Japanese people with T2D. We also identified resignation/surrender/acceptance of insulin as a reason for treatment commencement. This study provides important information to assist HCPs in helping reluctant Japanese people with T2D to initiate basal insulin therapy. Highlights: Many people with type 2 diabetes are reluctant to commence insulin treatment. Telephone interviews were used to identify factors motivating insulin initiation. Steps for Coding and Theorization, a qualitative data analysis method, was used. Health care provider actions can help alleviate reluctance to insulin initiation. Participants reported resignation/surrender/acceptance as a reason to commence insulin.